DETERMINAN PERILAKU KEWARGAAN ORGANISASI DI PEMERINTAH KOTA PALU - Arma, Ahmad Rijal; Syariati, Alim (Jurnal Minds: Manajemen Ide dan Inspirasi, 2015)
This study aims to investigate the determinants of organizational citizenship behavior at Palu local government. The collection of data through questionnaires took sample of 221 respondents. Sample criteria are high level officials such as the Head of Department or the Head of the Agency, administration level officials like administrators (Echelon III) and the official supervisors (Echelon IV), and functional level officials varied within functional expertise and skilled functional officials (supervisor positions) at least level III/c. Its Sampling technique is conducted by using multifarious or sampling combined with a combination of purposive sampling and stratified sampling (proportionate stratified random sampling). Data are analysed by using Structural Equation Modelling Partial Least Square (SEM PLS). The results reveal that (1) Public service motivation positively and significantly effect organizational citizenship behavior, and (2) Organizational commitment support the positive and significant effect on organizational citizenship behavior at Palu local government.